The Toll of War : The Economic and Social Consequences of the Conflict in Syria - World Bank (World Bank, Washington, DC, 2017)
The Arab Spring protests marked the beginning of a new era in the Syrian Arab Republic in 2011. Minor public protests began almost immediately after the initial protests in Cairo in January 2011. The first large demonstrations began two months later in March, and the following months saw a process of escalation as demonstrations spread and increased in size within the country. By the summer of 2011, the armed conflict was already unfolding. Now in its sixth year, the Syrian conflict remains active and is bringing much pain and tragedy on a daily basis. This study provides an assessment of the conflict’s impact on economic and social outcomes in Syria as of early 2017. The analysis focuses on taking stock of the effects of the conflict in four areas: (i) physical damage, (ii) loss of lives and demographic dispersion, (iii) economic outcomes, and (iv) human development outcomes.